Fourier transformant area deconvolution condition. Construction of the image degradation matrix (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2011)
Symbolic method of forming image degradation matrix at Adamar conversion transformants area is proposed. Algorythm of forming coefficients at distortion system impulse characteristics samples for any range of samples and product coefficients evaluation algorythm  were developed. Algorithm obtained differs in simplicity, symbolic expressions enable to increase matrix forming speed-performance for matrixes, those are used for image restavration algorythm with additive noize with method of conditional deconvolution. Symbolic expressions enable to notably increase accuracy of matrix elements evaluation, considering to limited operand dimensionality.